Experience of EU countries in organizing of the circulation and availability of medicines for the population - Zbrozhek, Svitlana (Actual Problems of Medicine and Pharmacy, 2021)
Finland's health care system has evolved over the years, with its distinctive features being tax funding, the provision of the vast majority of medicines and medical services by public and municipal authorities. to study the experience of EU countries in the field of health care in the organization of circulation and availability of medicines. To achieve this goal used the methods of regulatory, documentary, comparative and graphical analysis. The increase in the cost of medical care leads to the fact that the state is increasingly thinking about containing costs. The level of co-financing by patients is growing, at the same time measures are being taken to limit the selling price of medicines. The existing system of reference prices promotes the entry of generics into the market and, apparently, this direction will develop. A characteristic feature of the health care and pharmaceutical supply system in the Nordic countries is coordination, which is implemented at different levels and in many forms. The organization of the circulation and accessibility of medicines for the population in Finland is based on covering the costs of medicines through the social insurance system, but with the participation of the state. The priority common aspects of the functioning of the national health care systems of the Scandinavian region remain: coordination between hospitals and definition of their areas of activity; coordination between general services and specialized assistance centers; coordination of the organization of drug circulation and medical care for certain categories of patients (privileged categories, patients with oncological diseases, etc.); coordination of pharmaceutical support and medical services for patients with chronic diseases (diabetes, etc.); coordination of long-term pharmaceutical provision and medical care for the elderly.